SARS‐CoV‐2‐specific virulence factors in COVID‐19. Issue 3 (1st November 2020) - Kumar, Ashutosh; Prasoon, Pranav; Kumari, Chiman; Pareek, Vikas; Faiq, Muneeb A.; Narayan, Ravi K.; Kulandhasamy, Maheswari; Kant, Kamla
Abstract: The paucity of knowledge about severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)‐specific virulence factors has greatly hampered the therapeutic management of patients with coronavirus disease 2019 (COVID‐19). Recently, a cluster of studies appeared, which presented empirical evidence for SARS‐CoV‐2‐specific virulence factors that can explain key elements of COVID‐19 pathology. These studies unravel multiple structural and nonstructural specifics of SARS‐CoV‐2, such as a unique FURIN cleavage site, papain‐like protease (SCoV2‐PLpro), ORF3b and nonstructural proteins, and dynamic conformational changes in the structure of spike protein during host cell fusion, which give it an edge in infectivity and virulence over previous coronaviruses causing pandemics. Investigators provided robust evidence that SARS‐CoV‐2‐specific virulence factors may have an impact on viral infectivity and transmissibility and disease severity as well as the development of immunity against the infection, including response to the vaccines. In this article, we are presenting a summarized account of the newly reported studies.